Exploring Swedish veterinarians' awareness of non-accidental-injuries, animal abuse and the Link to domestic violence, and their role in addressing this societal issue - Oellig, Lisa; Lindsjö, Johan; Röcklinsberg, Helena (Frontiers in Veterinary Science, 2024)
Research has established a link between animal abuse and domestic violence (the Link), where the perpetrator uses the animal to control the human victim. Veterinarians are exposed to both vulnerable animals and humans, playing a crucial role in detecting and handling these cases. A study using an online survey was conducted in 2019, exploring the awareness of Swedish veterinarians regarding Non-accidental-injuries (NAI) in animals, the Link between animal abuse and domestic violence and how to handle such cases. The survey was distributed by the Swedish Veterinary Association to 2,627 licensed veterinarians and was answered by 362 respondents. One of ten had experienced the Link in their clinical work while 63% did not know if they had. The awareness of the Link was generally high (90%), whereas 68% of respondents answered that they did not know or were unsure about the concept of NAI. Almost half of the respondents (44%) felt that they were unsure about how NAI should be diagnosed, 56% did not know how NAI should be documented and a third (34%) did not know which authority should be contacted in case of suspicion of animal abuse. A minority, 17%, knew how to act when there was a reason to suspect domestic violence. The responses showed that support in the clinics is inadequate, with only 10% stating that information material and further education is offered about the Link and 17% knew of action plans or procedures for dealing with a suspected case of animal abuse. Only 16% stated that the Link was part of their education. Improving the ability of veterinarians to act appropriately requires more integrated theoretical and practical training during their university studies. At the clinic, further education, action plans and collaboration with competent authorities and organizations are crucial. It is important that resources, such as information material, guidelines, action plans and educational programs are identified and used to support veterinarians in their work to help vulnerable animals and, by extension, people, in line with the concept of One Welfare.